Psikoedukasi Pengelolaan Emosi sebagai Upaya Pencegahan Kenakalan Anak dan Remaja di SMP Negeri 3 Tanjung Lago - Amaliyah, Rizky; Elysia, Aldora Cinta (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aimed to provide education on emotional regulation and delinquency prevention for students at SMP Negeri 3 Tanjung Lago. The methods used were psychoeducation and group counseling, with 17 students as the main participants. Six students who had more prominent problems in emotional management were further included in group counseling. This program was carried out in four sessions: one psychoeducation session and three group counseling sessions. Based on the results, it can be concluded that the program was implemented properly and achieved the stipulated goals. Psychoeducation about emotional regulation has succeeded in increasing students' knowledge about the types of emotions and how to manage them positively and adaptively. Students were able to identify emotional triggers, practice self-regulation techniques such as butterfly hug, positive self-talk, and reappraisal, develop empathy and assertive communication skills. An increase was seen from observations during activities and from pre-test and post-test scores after psychoeducational intervention. In general, this program is effective as a preventive effort against Juvenile delinquency by fostering a positive character in school environments.